New research directions on disparities in obesity and type 2 diabetes. Issue 1 (3rd December 2019) - Thornton, Pamela L.; Kumanyika, Shiriki K.; Gregg, Edward W.; Araneta, Maria R.; Baskin, Monica L.; Chin, Marshall H.; Crespo, Carlos J.; de Groot, Mary; Garcia, David O.; Haire‐Joshu, Debra; Heisler, Michele; Hill‐Briggs, Felicia; et al.
Abstract: Obesity and type 2 diabetes disproportionately impact U.S. racial and ethnic minority communities and low‐income populations. Improvements in implementing efficacious interventions to reduce the incidence of type 2 diabetes are underway (i.e., the National Diabetes Prevention Program), but challenges in effectively scaling‐up successful interventions and reaching at‐risk populations remain. In October 2017, the National Institutes of Health convened a workshop to understand how to (1) address socioeconomic and other environmental conditions that perpetuate disparities in the burden of obesity and type 2 diabetes; (2) design effective prevention and treatment strategies that are accessible, feasible, culturally relevant, and acceptable to diverse population groups; and (3) achieve sustainable health improvement approaches in communities with the greatest burden of these diseases. Common features of guiding frameworks to understand and address disparities and promote health equity were described. Promising research directions were identified in numerous areas, including study design, methodology, and core metrics; program implementation and scalability; the integration of medical care and social services; strategies to enhance patient empowerment; and understanding and addressing the impact of psychosocial stress on disease onset and progression in addition to factors that support resiliency and health. Abstract : This report discusses a workshop convened by the National Institutes of Health to understand how to (1) address socioeconomic and other environmental conditions that perpetuate disparities in the burden of obesity and type 2 diabetes; (2) design effective prevention and treatment strategies that are accessible, feasible, culturally relevant, and acceptable to diverse population groups; and (3) achieve sustainable health improvement approaches in communities with the greatest burden of these diseases.